2017
DOI: 10.1021/acs.nanolett.7b01505
|View full text |Cite
|
Sign up to set email alerts
|

Coherent Interlayer Tunneling and Negative Differential Resistance with High Current Density in Double Bilayer Graphene–WSe2 Heterostructures

Abstract: We demonstrate gate-tunable resonant tunneling and negative differential resistance between two rotationally aligned bilayer graphene sheets separated by bilayer WSe. We observe large interlayer current densities of 2 and 2.5 μA/μm and peak-to-valley ratios approaching 4 and 6 at room temperature and 1.5 K, respectively, values that are comparable to epitaxially grown resonant tunneling heterostructures. An excellent agreement between theoretical calculations using a Lorentzian spectral function for the two-di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 49 publications
(121 reference statements)
0
43
0
Order By: Relevance
“…Several recent reports suggested [19] [20] that twisted layers of 2D materials can modify the transport properties of the stacked layers significantly. This method of forming heterostructures using 2D materials can significantly modify the band-structure and hence transport properties [19][20] [21].…”
Section: Introductionmentioning
confidence: 99%
“…Several recent reports suggested [19] [20] that twisted layers of 2D materials can modify the transport properties of the stacked layers significantly. This method of forming heterostructures using 2D materials can significantly modify the band-structure and hence transport properties [19][20] [21].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, using TMDs with a smaller bandgap as tunnel barriers may enhance the peak-to-valley ratio of the resonances in the electrical characteristics. Recently, Burg et al [78] demonstrated gate-tunable resonant tunneling and NDR between two rotationally-aligned bilayer Gr sheets separated by a bilayer WSe 2 . Remarkable large interlayer current densities of 2 µA/µm 2 and NDR peak-to-valley ratios of~4 were observed at room temperature in these device structures.…”
Section: Resonant Interlayer Tunneling Transistorsmentioning
confidence: 99%
“…Resonate tunneling current and negative differential resistance (NDR) have been observed in graphene‐based heterostructure TFETs, including monolayer and bilayer graphene separated by BN25, 26, 27, 28, 29, 30 or TMDs 6, 31. However, due to the absence of a bandgap, graphene‐based TFETs are unable to obtain a high on/off ratio of the current.…”
Section: Introductionmentioning
confidence: 99%